Foetal Growth Restriction in Children with Prothrombotic Risk Factors - Kries, Rüdiger von; Junker, Ralf; Oberle, Doris; Kosch, Andrea; Nowak-Göttl, Ulrike (Thrombosis and Haemostasis, 2001)
Placental infarction is frequently observed in low birth weight children. To evaluate whether low birth weight in healthy term neonates is associated with foetal inherited prothrombotic risk factors this retrospective study was conducted. Outcome measures were “birth weight in the lowest quartile” and “birth weight in the lowest decile” in singletons with a gestational age of ≥37 weeks.The analyses were based on 375 Caucasian children screened at the Münster childhood thrombophilia centre with complete data for all prothrombotic risk factors (factor V G1691A, prothrombin G20210A, elevated lipoprotein (a), protein C-, protein S-, antithrombin-deficiency). The proportion of children in the lowest birth weight quartile increased from 23.7% to 30.5% to 48.0% for children with no, only single heterozygous and multiple or homozygous defects respectively. The respective adjusted odds ratios (95% confidence intervals) of thrombophilia for birth weight in the lowest quartile (lowest decile) were 1.53 (0.76-3.08) in carriers of one prothrombotic risk factor and 4.01 (1.48-10.84) in subjects carrying multiple or homozygous defects. We identified foetal thrombophilia as an additional cause of low birth weight.
Keywords: Foetal growth restriction; factor V G1691A; prothrombin G20210A; lipoprotein (a); protein C; protein S; antithrombin